The Glycolytic Metabolite, Fructose-1,6-bisphosphate, Blocks Epileptiform Bursts by Attenuating Voltage-Activated Calcium Currents in Hippocampal Slices - Shao, Li-Rong; Wang, Guangxin; Stafstrom, Carl E. (Frontiers in Cellular Neuroscience, 2018)
Manipulation of metabolic pathways (e.g., ketogenic diet (KD), glycolytic inhibition) alters neural excitability and represents a novel strategy for treatment of drug-refractory seizures. We have previously shown that inhibition of glycolysis suppresses epileptiform activity in hippocampal slices. In the present study, we aimed to examine the role of a “branching” metabolic pathway stemming off glycolysis (i.e., the pentose-phosphate pathway, PPP) in regulating seizure activity, by using a potent PPP stimulator and glycolytic intermediate, fructose-1,6-bisphosphate (F1,6BP). Employing electrophysiological approaches, we investigated the action of F1,6BP on epileptiform population bursts, intrinsic neuronal firing, glutamatergic and GABAergic synaptic transmission and voltage-activated calcium currents (ICa) in the CA3 area of hippocampal slices. Bath application of F1,6BP (2.5–5 mM) blocked epileptiform population bursts induced in Mg2+-free medium containing 4-aminopyridine, in 2/3 of the slices. The blockade occurred relatively rapidly ( 4 min), suggesting an extracellular mechanism. However, F1,6BP did not block spontaneous intrinsic firing of the CA3 neurons (when synaptic transmission was eliminated with DNQX, AP-5 and SR95531), nor did it significantly reduce AMPA or NMDA receptor-mediated excitatory postsynaptic currents (EPSCAMPA and EPSCNMDA). In contrast, F1,6BP caused moderate reduction ( 50%) in GABAA receptor-mediated current, suggesting it affects excitatory and inhibitory synapses differently. Finally and unexpectedly, F1,6BP consistently attenuated ICa by 40% without altering channel activation or inactivation kinetics, which may explain its anticonvulsant action, at least in this in vitro seizure model. Consistent with these results, epileptiform population bursts in CA3 were readily blocked by the nonspecific Ca2+ channel blocker, CdCl2 (20 μM), suggesting that these bursts are calcium dependent. Altogether, these data demonstrate that the glycolytic metabolite, F1,6BP, blocks epileptiform activity via a previously unrecognized extracellular effect on ICa, which provides new insight into the metabolic control of neural excitability.